Pengaruh Kesadaran Wajib Pajak, Pelayanan Perpajakan dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Bukittinggi - Ikhmah Ramadani; Amsah Hendri Doni (Transformasi: Journal of Economics and Business Management, 2024)
This research is that there is still a lack of awareness among taxpayers to report/pay taxes through the tax service office due to lack of socialization, awareness, lack of tax services and lack of emphasis on tax sanctions. This research aims to determine the influence of taxpayer awareness, tax services and tax sanctions on individual taxpayer compliance. Method: Data was collected through primary data documentation. This type of research is descriptive quantitative. Then a method is carried out which includes data prerequisite tests consisting of (Normality Test and Reliability Test), then the Classical Assumption Test consisting of (Autocorrelation Test, Homogeneity Test and Multicollinearity Test and Heteroscedasticity Test) then Multiple linear regression test, then Coefficient of Determination Test, then Test The hypothesis consists of (Partial Test and Simultaneous Test). To analyze using SPSS 24.0 software. The basis used in this research uses compliance theory. Research Results: Based on the results of the tests carried out, the following conclusions can be put forward: 1) Taxpayer awareness (KWP) has a positive and significant effect on individual taxpayer compliance at KPP Pratama Bukittinggi in 2022 by finding a result of 0.051<0.05, so Ho is rejected. 2) Tax Services for Individual Taxpayer Compliance in 2022 with results of 0.005>0.05 Ho being accepted. 3) Tax sanctions for individual taxpayer compliance in 2022 with results of 0.001>0.05 Ho accepted. 4) simultaneously KWP, PP and SP have a significant effect on KWPOP by finding a result of 0.000>0.05 so Ho is rejected and Ha is accepted. Analysis of the findings shows that Taxpayer Awareness (KWP), Tax Services (PP) and tax sanctions (SP) affect individual taxpayer compliance due to an increase in taxpayers which will ultimately affect State income.